2021
DOI: 10.1029/2020jb020202
|View full text |Cite
|
Sign up to set email alerts
|

Compactive Deformation of Sandstone Under Crustal Pressure and Temperature Conditions

Abstract: The weakening is greater in the ductile regime than in the brittle regime. 10• A lowering of the fracture toughness can explain the observed weakening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
(135 reference statements)
0
5
0
Order By: Relevance
“…In siliclastics, Jefferd et al. (2021) showed that the pressure of the brittle to ductile transition decreases from 20°C to 150°C in water‐saturated sandstone which they attributed to enhanced cataclastic pore collapse, a conclusion consistent with the observation that cataclasis is prevalent in siliclastic rocks at low temperatures. This is similar to our conclusion in the Solnhofen limestone but more expected as cataclastic pore collapse operates under dry conditions in sandstones as well (Wong et al., 1997).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In siliclastics, Jefferd et al. (2021) showed that the pressure of the brittle to ductile transition decreases from 20°C to 150°C in water‐saturated sandstone which they attributed to enhanced cataclastic pore collapse, a conclusion consistent with the observation that cataclasis is prevalent in siliclastic rocks at low temperatures. This is similar to our conclusion in the Solnhofen limestone but more expected as cataclastic pore collapse operates under dry conditions in sandstones as well (Wong et al., 1997).…”
Section: Discussionmentioning
confidence: 63%
“…(2017) saw no measurable effect of temperature on K IC in dry calcite. The effect of temperature under water‐saturated conditions is unknown, but (Jefferd et al., 2021) a 2%–3% reduction in K IC in sandstone between 20°C and 150°C, which explained water weakening of the peak strength. Thus the effect may be small but non‐negligible in calcite as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable research has confirmed that the friction coefficient exhibits a rate-temperature-stress state dependence (Barbot, 2022;Blanpied et al, 1995;Pranger et al, 2022;Scholz, 2019;Zhang & Ma, 2021). Furthermore, temperature also has a significant influence on fracture toughness and cohesion (Guo et al, 2023;Jefferd et al, 2021;Suo et al, 2020;Xu et al, 2023;C. X. Zhao, Liu, et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research has confirmed that the friction coefficient exhibits a rate‐temperature‐stress state dependence (Barbot, 2022; Blanpied et al., 1995; Pranger et al., 2022; Scholz, 2019; Zhang & Ma, 2021). Furthermore, temperature also has a significant influence on fracture toughness and cohesion (Guo et al., 2023; Jefferd et al., 2021; Suo et al., 2020; Xu et al., 2023; C. X. Zhao, Liu, et al., 2023). However, it is regrettable that existing constitutive modeling efforts often resort to constant assumptions or curve fitting to describe the temperature response of mechanical characteristics such as strength, deformation, and damage of geological materials, lacking comprehensive consideration of the temperature‐dependent micromechanical mechanisms of fundamental mechanical properties like the friction coefficient, fracture toughness, and damage evolution.…”
Section: Introductionmentioning
confidence: 99%